Development of Google Sites-Based Learning Media to Increase Students Motivation to Learn Science at Elementary School 2 Kedungsoko - Widyawati, Diah Windi; Rindrayani , Sulastri Rini (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to develop Google Sites-based learning media to improve students' learning motivation in Natural and Social Sciences (IPAS) subjects at SD Negeri 2 Kedungsoko. This learning media is designed as an interactive platform that contains materials, learning videos, quizzes, and discussion forums that are easily accessible to students. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study were fifth grade students with a sample size of 30 people. Data were collected through learning motivation questionnaires, interviews, and observations before and after the implementation of learning media. The results of the study showed that the use of Google Sites as a learning media significantly increased students' learning motivation. This is indicated by an increase in the average score of the learning motivation questionnaire by 25% after using the media. Students feel more interested and motivated because the material is presented in an interesting, interactive, and flexible manner according to their needs. In addition, teachers also provide positive feedback on the ease of use and effectiveness of this media. Thus, Google Sites-based learning media can be an innovative alternative in supporting a more interesting and effective IPAS learning process in elementary schools